Transaction cost economics: The natural progression: Wykład noblowski wygłoszony 8 grudnia 2009 r. z wprowadzeniem Boba Jessopa - Williamson, Oliver E. (Journal of Public Governance, 2015)
The research program on which I and others have been working has been variously described as the “economics of governance,” the “economics of organization,” and “transaction cost economics.” As discussed in Section 1, governance is the overarching concept and transaction cost economics is the means by which to breathe operational content into governance and organization. The specific issue that drew me into this research project was the puzzle posed by Ronald Coase in 1937: What efficiency factors determine when a firm produces a good or service to its own needs rather than outsource? As described in Section 2, my 1971 paper on “The Vertical Integration of Production” made headway with this issue and invited follow-on research that would eventually come to be referred to as transaction cost economics. The rudiments of transaction cost economics are set out in Section 3. Puzzles and challenges that arose and would require “pushing the logic of efficient governance to completion” are examined brief ly in Section 4. Concluding remarks follow.